Antioxidant activity study and GC-MS profiling of leaves, stem and root extracts of Spermadictyon suaveolens Roxb. - Padinjarekutt, Divya Lobo; Aparna Saraf, Aparna Saraf (Academia Journal of Biology, 2024)
The characterization of bioactive components in the methanolic and isopropyl alcoholic plant extracts of Spermadictyon suaveolens Roxb. (Rubiaceae) was undertaken with the help of GC-MS technique, followed by the study of free-radical scavenging capabilities of the plant hydroalcoholic extracts using DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) test technique with ascorbic acid as the standard. There’s a constant formation of free radicals in the human body tissues originating due to the oxidation of specific chemical components, whereas the antioxidant molecules prevent or inhibit this free radical formation that may lead to lifelong or terminal diseases. The comparison of the antioxidant capacity of the plant extracts with that of the standard revealed that the leaf extracts showed maximum inhibition of DPPH, or radical scavenging activity. The EC50 values of ascorbic acid, leaves, stem, and root were found to be 18.62 µg/mL, 44.668 µg/mL, 89.125 µg/mL, and 97.723 µg/mL, respectively. The different peaks in the GC-MS analysis spectrum determined 24, 19, and 26 phytochemicals in leaves, stems, and roots, respectively. Out of all the phytoconstituents found, the major ones were n-Hexadecanoic acid or palmitic acid, squalene, 1.4-tert-Butylcalix[4]arene, and 1.3,5-Dihydroxy-6-methyl-2,3-dihydro-4H-pyran-4-one in leaves. 11-Bromoundecanoic acid, Ethylhexanol, Tetratetracontane, 2-Decanol, Propanoate in Stem, and n-Hexadecanoic acid 9,12-Octadecadienoic acid (Z,Z), 4,6-Bis(4-fluoro-3-(trifluoromethyl) phenoxy)-2-pyrimidinol, squalene in roots. Thus, the different bioactive constituents found to be present in the plant under study prove that the plant has the capacity to exhibit good antioxidant and other pharmacological properties.